2015
DOI: 10.2308/isys-51284
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Frequency and Presentation Format: Detecting Real Activities Manipulation

Abstract: As management increasingly manages earnings through real activities manipulation (RAM), RAM detection has become an important issue. This study investigates the role of reporting frequency and presentation format in detecting sales-related RAM. Based on the results of an online experiment with 77 experienced financial analysts, we find that more frequent financial reporting significantly improves sales-related RAM detection when financial analysts are aided with graphical displays. The results of our study sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…The practice of REM is more costly from the perspective of shareholders and investors (Chi, Lisic, & Pevzner, 2011; Zang, 2012) because it is associated with low‐quality cash flow information (Roychowdhury, 2006), exacerbated information asymmetry, less credible and reliable accounting numbers (Ascioglu, Hegde, Krishnan, & McDermott, 2012) and severe economic consequences (Tang, Eller, & Wier, 2016). Thus, finding a mechanism to eliminate REM has become of increasing interest to several types of stakeholder over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The practice of REM is more costly from the perspective of shareholders and investors (Chi, Lisic, & Pevzner, 2011; Zang, 2012) because it is associated with low‐quality cash flow information (Roychowdhury, 2006), exacerbated information asymmetry, less credible and reliable accounting numbers (Ascioglu, Hegde, Krishnan, & McDermott, 2012) and severe economic consequences (Tang, Eller, & Wier, 2016). Thus, finding a mechanism to eliminate REM has become of increasing interest to several types of stakeholder over the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental accounting research has shown that graphs change the perception of investors and accountants about corporate performance (Tang et al, 2016). Furthermore, the impression management of graphs, especially through the use of selectivity techniques, is especially effective on the most impulsive analysts (Cardoso et al, 2015).…”
Section: Legitimacy Theory and Visual Contentmentioning
confidence: 99%
“…Hasil tersebut sesuai dengan penelitian Khan (2015), Tang, Eller, & Wier (2016), dan Yusuf (2013) yang menjelaskan jika umur terdaftar perusahaan tidak memiliki pengaruh ketetapan waktu CIR. Namun, penelitian ini bertolak belakang dengan temuan beberapa peneliti (Botti, Boubaker, Hamrouni, & Solonandrasana, 2014;Dolinšek & Lutar-Skerbinjek, 2018;Guillamón Saorín & Martínez López, 2013).…”
Section: Metodeunclassified
“…Penelitian yang dilakukan oleh Rini (2016) dan Tang, Eller, & Wier (2016) sesuai dengan temuan dalam pengujian ini, yaitu struktur kepemilikan publik tidak dapat memacu ketepatan waktu pelaporan keuangan. Meskipun demikian, penelitian ini justru menolak temuan Alsartawi (2018) Implikasi dari pemberlakuan peraturan OJK tersebut menjadikan perusahaan Indonesia wajib untuk melaporkan laporan tahun an dan laporan keuangannya di web site.…”
Section: Metodeunclassified